Online requests for sexual pictures from youth: risk factors and incident characteristics. - Mitchell KJ; Finkelhor D; Wolak J (Journal of Adolescent Health, 2007)
PURPOSE: The aim of this study was to explore the prevalence and characteristics of youth who receive requests to make and send sexual pictures of themselves over the Internet. METHODS: Data were collected as part of the Second Youth Internet Safety Survey, a nationally representative telephone survey of 1,500 youth Internet users, ages 10-17 years, in the United States. RESULTS: Among Internet-using youth 4% reported an online request to send a sexual picture of themselves during the previous year. Only one youth of 65 sample case subjects actually complied. Being female, being of Black ethnicity, having a close online relationship, engaging in sexual behavior online, and experiencing physical or sexual abuse offline were risk factors for receiving a request for a sexual picture. Incidents that involved requests for sexual pictures were more likely to occur when youth were in the presence of friends, communicating with an adult, someone they met online, who had sent a sexual picture to the youth, and who attempted or made some form of offline contact with the youth. CONCLUSIONS: The findings from this study provide support for including requests for sexual pictures in the spectrum of online experiences about which pediatric and adolescent health professionals need to be knowledgeable. These findings also provide information about populations that need targeted prevention education about online dangers, namely vulnerable (e.g., abused boys and girls) and female Black youth.